Disadvantage and Privilege in our Schools: How Teachers, Psychologists and Policymakers can do Better. Issue 1 (22nd January 2014) - Williams, Wendy R.; Carter, Kristina A.
<x xml:space="preserve">Abstract</x> By examining the ways in which teachers address social class in an economically integrated school, White, Mistry, & Chow (2013) call attention to a critical gap in the educational system. Their analysis indicates that although teachers are comfortable discussing diversity in a number of areas, social class diversity is not covered with the same care as other domains. The current paper uses White at al. (2013) as a starting point to discuss how teachers, psychologists, and policy‐makers can better educate students about both social class privilege and disadvantage.